The Relationship between the Characteristics of the Respondents and the Satisfaction of the Elderly Using Squat Toilets - Rian yuliyana; Haryadi Haryadi; Arthia Diarina (Jurnal Ilmiah Keperawatan Indonesia [JIKI], 2019)
Increased life expectancy is in line with the increase in the number of elderly people from year to year. Elderly has many changes in the body. Changes in the body's system cause a lot of decrease in physical ability. The most dangerous and high risk space for the elderly is the bathroom. The bathroom is dangerous due to a decrease in physical ability which causes the safety of the elderly during activities such as defecation using a squat Water closet (WC). The purpose of this study was to determine the relationship between the characteristics of respondents and the satisfaction of the elderly using squat toilets. This research method uses descriptive correlation with cross sectional approach. The total population is 73 elderly in the Tanjung Pinang nursing home. The sample of this study was 43 elderly using simple random sampling technique. The analysis used is frequency, percentage and chisquare. This study also showed that sex and height were not related to satisfaction with the use of squatting lavatories, but age and weight had a relationship with the satisfaction of the elderly using squat toilets. The results of this study recommend the use of a sitting Water Closet that is comfortable and safe for the elderly. Keywords:characteristics of respondents, satisfaction of the eldely using squat toilet